Molecular Dynamic Simulation Study of the Diffusion of Gases in Water - LIU, QINGZHI (Asian Journal of Chemistry, 2010)
Using molecular dynamics simulation, the diffusion of 9 kinds of gases were simulated in the canonical number of atoms, volume and temperature (NVT) ensemble. The mean square displacement data were analyzed by the differentiation-interval variation method. The calculated values were compared with the experimentally obtained values found in the literature. The error between calculated diffusion coefficients and experimental values is between 14 and 37 %, which is less than 50 %. Moreover, analysis of the diffusion coefficient shows that the diffusion coefficients of the same system differ a lot when they were calculated with different samples. The diffusion coefficient of molecules in system containing maximum samples is more close to the experimental value than others. Sample has the same effect on diffusion coefficients at different temperature.